Diversidad de insectos beneficos asociados a Morinda citrifolia L. - Matienzo Brito, Y.=700 1 Rijo Camacho, E.; Milan Vargas, O.; Torres Nelson, N.; Larrinaga lewis, Y.; Romero Castillo, N.; Pla del Campo, D.
(Es, En)
Ilus., 10 ref.
Keywords: MORINDA CITRIFOLIA; INSECTOS UTILES; BIODIVERSIDAD; ESPECIES; CUBA